Cannabinoid compounds in combination with curcumin and piperine display an anti-tumorigenic effect against colon cancer cells - Yuksel, Busra; Deniz, Aysen Asli Hizli; Sahin, Fikrettin; Şahin, Kazım; Turkel, Nezaket (Frontiers Media Sa, 2023)
Currently, use of cannabinoids is limited to improve adverse effects of chemotherapy and their palliative administration during treatment is curiously concomitant with improved prognosis and regressed progression in patients with different tumor types. Although, non-psychoactive cannabidiol (CBD) and cannabigerol (CBG) display antineoplastic effects by repressing tumor growth and angiogenesis both in cell line and animal models, their use as chemotherapeutic agents is awaiting further investigation. Both clinical and epidemiological evidence supported by experimental findings suggest that micronutrients such as curcumin and piperine may present a safer strategy in preventing tumorigenesis and its recurrence. Recent studies demonstrated that piperine potentiates curcumin's inhibitory effect on tumor progression via enhancing its delivery and therapeutic activity. In this study, we investigated a plausible therapeutic synergism of a triple combination of CBD/CBG, curcumin, and piperine in the colon adenocarcinoma using HCT116 and HT29 cell lines. Potential synergistic effects of various combinations including these compounds were tested by measuring cancer cell proliferation and apoptosis. Our findings revealed that different genetic backgrounds of HCT116 and HT29 cell lines resulted in divergent responses to the combination treatments. Triple treatment showed synergism in terms of exhibiting anti-tumorigenic effects by activating the Hippo YAP signaling pathway in the HCT116 cell line.
Keywords: cannabidiol; cannabigerol; curcumin; piperine; colon cancer